(untitled) (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This research is motivated by the low level of student involvement in learning to write fiction due to the use of learning media that is still less interactive and has not been able to attract students’ attention optimally. This condition has an impact on low student participation in understanding the concepts and elements of fictional works. This study aims to develop interactive learning media based on Kahoot on fictional works material for eighth grade students of SMP Negeri 1 Hiliserangkai and to determine the level of feasibility and practicality of the developed media. This study uses the Research and Development (R&D) method with a 4D development model that includes the stages of define, design, develop, and disseminate. The research subjects were eighth grade students of SMP Negeri 1 Hiliserangkai. Data were collected through validation questionnaires from material experts, linguists, media experts, student response questionnaires, and documentation. Data were analyzed using quantitative descriptive analysis techniques based on the percentage of validation results and user responses. The results showed that the media obtained validation from material experts of 98%, linguists of 89%, and media experts of 93%. The practicality test obtained results of 81% in small groups and 96% in large groups. Thus, Kahoot-based learning media is declared feasible and practical for use in learning fictional works to increase student engagement.